World Bank Research Digest, Vol. 6(4) - World Bank (Washington, DC, 2014)
In this issue: restoring the Lustre of the European economic model; investing in the power sector; how much does Gross Domestic Product (GDP) increase when public spending increases? Inclusive green growth; what are the health effects of universal health care? Policy barriers to international trade in services; and using performance incentives to improve health outcomes.